Management of Community Acquired Respiratory Tract Infections with Co-morbidities - Balamurugan, Santhalingam (Indian Journal of Case Reports, 2015)
Community-acquired respiratory tract infections are one of the commonest infections seen in the clinical practice and animportant cause of mortality and morbidity, especially in patients with immune-compromised states. Two cases of antibiotic resistant community-acquired lower respiratory tract infections in a 42-year-old male and a 68-year-old male are reported. Both had presented with lower respiratory tract symptoms, previously treated with antibiotics. The patients were immunecompromised and suffered from conditions such as Diabetes and COPD. Along with this, they had an infection caused by resistant bacteria. The clinical history, investigations and the appropriate line of treatment selected in order to resolve complications in the present cases are detailed here.